The future is flexible? Exploring expert visions of energy system decarbonisation. (June 2021) - Groves, Christopher; Henwood, Karen; Pidgeon, Nick; Cherry, Catherine; Roberts, Erin; Shirani, Fiona; Thomas, Gareth
Highlights: Future imaginaries of energy systems are important in how the transition to a decarbonised energy system is governed. Demonstrator projects do not just reflect assumptions about the systems they are part of; they also test the credibility of these future imaginaries. Values and visions linked to demonstrator projects can provide sources of critical reflection on the credibility of system imaginaries. Data from a flexible energy systems project in south Wales, UK shows how experts are involved in the production of these localised imaginaries. Abstract: Decarbonising the energy system means moving from a centralised, fossil fuel-dependent one to one based primarily on renewable energy. Visions of whole system change focus on socio-technical concepts like electrification and flexibility, rather than single technologies such as nuclear or solar. The role that technological niches might play in relation to such systemic socio-technical visions is under-researched. Traditionally, technological niches are thought to nurture new 'proto-regimes', supported by coherent visions of how technologies will help solve problems within existing socio-technical regimes. However, the relationship between socio-technical visions like flexibility and individual demonstrator projects is more complex. Interviews with experts from the FLEXIS energy systems project (south Wales, UK) show how future visions associated with a range of demonstrator projects are being developed against the backdrop of a system-level vision of a flexible, multi-vector energy system. Interview data also shows how the development of visions for demonstrators draws on social learning about place and societal values overlooked in systemic visions. Such social learning can incorporate critical reflection on key assumptions that underlie dominant system-level visions. The extent such learning is possible through the development of potential niches, however, is subject to limitations that invite further research.